THEORETICAL JUSTIFICATION OF THE MANAGEMENT CONCEPT OF PROFESSIONAL DEVELOPMENT OF SCIENTIFIC AND PEDAGOGICAL STAFF OF THE MUNICIPAL ESTABLISHMENT OF HIGHER EDUCATION - Odarchenko, Veronika (Mountain School of Ukrainian Carpaty, 2023)
The article is devoted to the problem of development and theoretical justification of the author's vision of the concept of managing the professional development of scientific and pedagogical workers of a municipal establishment of higher education. The analysis of scientific and pedagogical literature made it possible to identify important provisions that were taken into account when developing the concept. The goal of the concept is determined, which consists in improving the system of effective management of professional development of scientific and pedagogical workers for the sustainable development of a municipal establishment of higher education and correlation with the educational goals of the region. Tasks have been formed, the implementation of which will allow us to achieve the main goal: anticipatory nature of the sustainable professional growth of scientific and pedagogical workers; priority directions for improving the efficiency of management activities; expanding opportunities for professional growth; creation of organizational and pedagogical conditions. The author has determined the directions and stages (preparatory, planning and design, implementation, verification of the concept) of the implementation of the concept of managing the professional development of scientific and pedagogical workers of a municipal establishment of higher education in modern conditions. The expected result of the implementation of the concept, which consists in increasing the professionalism of scientific and pedagogical workers, ensuring proactive nature in managing the professional development of scientific and pedagogical workers of a municipal establishment of higher education, is highlighted; improvement of management in higher education, etc. The author notes the possible risks that may arise in the process of implementing the developed concept into the educational content of communal institutions of higher education, including: a decrease in the motivation of scientific and pedagogical workers for professional growth; inconsistency of methods of professional development to the personal and professional demands of specialists; the unforeseen influence of external factors on the process of managing the professional development of scientific and pedagogical workers at the state and regional levels; insufficient funding, provision of the material and technical base, etc.